2021
DOI: 10.3390/cells11010073
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic EMT Phenotype Is Governed by MicroRNA-200-Mediated Competing Endogenous RNA Networks

Abstract: Epithelial–mesenchymal transition (EMT) is a fundamental physiologically relevant process that occurs during morphogenesis and organ development. In a pathological setting, the transition from epithelial toward mesenchymal cell phenotype is hijacked by cancer cells, allowing uncontrolled metastatic dissemination. The competing endogenous RNA (ceRNA) hypothesis proposes a competitive environment resembling a large-scale regulatory network of gene expression circuits where alterations in the expression of both p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 164 publications
(210 reference statements)
0
2
0
Order By: Relevance
“…In conclusion, our study confirmed that silencing lncRNA PCED1B-AS1 directly regulates miR-3681-3p/MAP2K7 signaling axis and inhibited proliferation, invasion and EMT processes of gastric cancer cell lines. More and more reports have confirmed that non-coding RNAs have complex regulatory networks, that is, multiple downstream target molecules, which regulated disease progression in multiple ways [ 27 ]. Therefore, the downstream molecule of lncRNA PCED1B-AS1 in the progression of gastric cancer needs to be further studied to clarify its specific marker in gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, our study confirmed that silencing lncRNA PCED1B-AS1 directly regulates miR-3681-3p/MAP2K7 signaling axis and inhibited proliferation, invasion and EMT processes of gastric cancer cell lines. More and more reports have confirmed that non-coding RNAs have complex regulatory networks, that is, multiple downstream target molecules, which regulated disease progression in multiple ways [ 27 ]. Therefore, the downstream molecule of lncRNA PCED1B-AS1 in the progression of gastric cancer needs to be further studied to clarify its specific marker in gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship of ceRNAs to outcomes in TNBC is typically a result of the direct effects on disease progression, e.g., metastasis. As discussed previously, ceRNA networks with miR-200 family members as central factors in controlling EMT and metastatic phenotypes in TNBC and other cancers [ 24 , 46 , 95 ]. Specific lncRNAs have been found to affect or predict metastasis of TNBC to specific sites.…”
Section: Significance Of Cernets Alterations In Tnbcmentioning
confidence: 99%